A Feasibility Study of Constructed Wetlands As Alternative to Sewerage System on Tourism – Based Island: A Case Study of Kampung Salang, Tioman Island - Suhaily, Saleh (2023)
The most widespread environmental problem affecting almost all island countries is the safe disposal of liquid domestic wastes, particularly human waste and sewage disposal. Few countries have adequate waste collection and treatment facilities even in the most developed urban areas, and those that exist are costly and seldom properly maintained. In spite of considerable efforts at rural sanitation, facilities in many rural areas are still rudimentary or entirely lacking. Tioman Island has population of 3,700 people and receive approximately 250,000 tourists yearly. With the land area of 145.08 sq. km or 14,508.80 ha, Tioman Island has highest ground elevation value of 1035 m. There are 36 rivers in the island that flow along the coast before discharging into the sea naturally. The research is based on the study on the feasibility study of constructed wetlands as alternative to sewerage system in island. From the site visit, it was decided that the most suitable site for the feasibility study was Kampung Salang, due to the availability and easiness of access to a gazetted Jabatan Perkhidmatan Pembetungan (JPP) land with a 0.52 ha area. Based on the population trend analysis of Kampung Salang, it was found out that Kampung Salang will only achieve 1000 Population Equivalent (PE) in another 30 years, which is the year 2050. If this trend continues, Kampung Salang will achieve a population of 2000 PE in year 2135. Water quality condition of Kampung Salang was investigated during dry season, wet season and high peak season through four sampling rounds, from July 2020 until September 2020. It was found that water quality at most downstream of Sungai Salang which is at WQ6 was classified in Class V. Malaysia National Water Quality Index (WQI).